Increased efficiency of a metalworking SME through process redesign using SMED, Poka Yoke and Work Standardization - Huertas-Reyes, Anell (2022)
After the difficult period during the year 2020, the metal-mechanic sector has been characterized by its high participation in the Peruvian GDP. However, by not having established working methods, productivity in the production process is affected and in comparison, at national level, companies in other sectors have an efficiency greater than 80% in their processes, which generates an increase in competition. This article intends to incorporate to the literature through the combination of Lean Manufacturing tools: The SMED tool will be used for the reduction of Set Up times; Poka Yoke, to avoid human errors through a mold that will prevent defects in the bending machine and through the standardization of work, to establish best practices in the various manufacturing processes of metal racks. The main result of this proposal is the reduction of man-hours lost in non-value generating activities to increase efficiency in the analyzed processes of the organization.